2016
DOI: 10.1038/ncomms12264
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic depth profiles of magneto-ionic heterostructures beyond the interface limit

Abstract: Electric field control of magnetism provides a promising route towards ultralow power information storage and sensor technologies. The effects of magneto-ionic motion have been prominently featured in the modification of interface characteristics. Here, we demonstrate magnetoelectric coupling moderated by voltage-driven oxygen migration beyond the interface in relatively thick AlOx/GdOx/Co(15 nm) films. Oxygen migration and Co magnetization are quantitatively mapped with polarized neutron reflectometry under e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
135
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 53 publications
1
135
0
Order By: Relevance
“…If the exchange coupling dominates, then the scale should be comparable to the exchange length (typically below 10 nm 60 ), otherwise the scale should be comparable to the thickness of the interfacial oxide (FeO x or CoO x ) monolayer (below 0.2 nm) 160 . As a further complication, in a Co/GdO x /AlO x magnetoelectric heterostruture where the Co film is relatively thick (15 nm), a very recent study by Gilbert et al 29 revealed that the interfacial oxidation mechanism can remain active through the entire Co film, not limited to the interface region.…”
Section: Microscopic Origins Of Magnetoelectric Coupling Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the exchange coupling dominates, then the scale should be comparable to the exchange length (typically below 10 nm 60 ), otherwise the scale should be comparable to the thickness of the interfacial oxide (FeO x or CoO x ) monolayer (below 0.2 nm) 160 . As a further complication, in a Co/GdO x /AlO x magnetoelectric heterostruture where the Co film is relatively thick (15 nm), a very recent study by Gilbert et al 29 revealed that the interfacial oxidation mechanism can remain active through the entire Co film, not limited to the interface region.…”
Section: Microscopic Origins Of Magnetoelectric Coupling Mechanismsmentioning
confidence: 99%
“…27 Overall, current fundamental understanding of these experimental observations is largely qualitative. In the case of a Co/ gadolinium-oxide system, [26][27][28][29] it was proposed that the coupling is enabled through a voltage modulation of the surface oxygen vacancy concentration of the dielectric (see Fig. 2c) and thereby the degree of interfacial Co oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides information about irreversible magnetic switching [29,30], magnetic interactions [31][32][33], distributions of magnetic characteristics [34,35], and magnetic phase separation [36,37], which are not easily accessible in conventional hysteresis loop investigations. While most FORC studies have been based on magnetometry measurements (M-FORC), recently the FORC methodology has also been extended to transport measurements such as magnetoresistance curves (MR-FORC) to probe spin disorder [38], and temperature-dependent resistivity measurement to investigate first order phase transitions [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Voltage-induced oxidation of thin Co layers from adjacent GdO x layers has been demonstrated in two-terminal structures as a means to realize the electric field control of magnetization and magnetic anisotropy. [18][19][20] Three-terminal solid state a smay@coe.drexel.edu electric double layer transistors using a Gd-doped CeO 2 gating layer have been explored, demonstrating that the source-drain current across a SrTiO 3 (STO) channel can be increased by up to four orders of magnitude with gate voltages above 2 V. 21 The mechanism behind this phenomenon was attributed to the accumulation of oxygen anions at the Gd-doped CeO 2 /STO interface, which modifies the conductivity in the STO at the interface. These three-terminal devices represent a novel platform for controlling various functional properties via the electrostatic modulation of oxygen anions and vacancies and motivate our study exploring the use of a gate bias applied across a solid-state electrolyte to manipulate the oxygen concentration in the adjacent ferrite perovskite channel.…”
mentioning
confidence: 99%